University Educational District as an Innovative Corporation and Education Management Entity - Islamov, Artem E.; Nikonova, Svetlana I.; Timonin, Andrey I.; Dobrovolskaya, Liana V.; Dyadyunova, Irina A.; Timirov, Fedor F.; Koridze, Mikhail T.; Mukhamedzhanova, Bella A. (International Review of Management and Marketing, 2016)
Relevance of the paper is caused by the regionalization of education and the development of organizational and managerial innovations in the education system. The aim of the article is to reveal features of the University educational district as an innovative Corporation and the entity of education management. The leading method is the method of action research (AR), allowing to obtain new knowledge about University educational district, as innovative Corporation and the entity of education management and to develop a mechanism for the formation of regional educational environment. The article reveals the essence of the university educational district as an open and accountable social institution for society; determines the content of the regional educational environment, providing an efficient interaction of all the entities of educational policy in the region; represents a mechanism of formation of the regional educational environment aimed at sustainable development of the region. Article Submissions may be useful for research and teaching staff of vocational educational system, specialists of education authorities and regional authorities. Keywords: Management of Education, University Educational District, Regionalization of Education. JEL Classifications: I25, M14, O35